Hubungan Pengelolaan Kelas terhadap Hasil Belajar Siswa - Rahmayanti, Zikrillah (Mitra PGMI: Jurnal Kependidikan MI, 2021)
The purpose of this study was to determine the relationship between classroom management and students' learning outcomes at grade IV SDN 010 Tembilahan Hulu. This type of research was quantitative research. The data in this study were collected using questionnaires, documentation and analyzed using product-moment correlation with the help of SPSS 22.0. The results of the data analysis showed that the value of sig. (2-tailed) between classroom management (x) and learning outcomes (y) was 0.000 <0.05, which means that there was a significant correlation between classroom management variables and learning outcomes. The calculated r-value for the relationship between classroom management (x) and learning outcomes (y) was 0.642 > from 0.374, so it can conclude that there was a relationship or correlation between classroom management and learning outcomes. Because the calculated r in this analysis was positive, meaning that the relationship between the two variables was positive.